2019
DOI: 10.1016/j.anai.2018.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Dupilumab improves symptoms, quality of life, and productivity in uncontrolled persistent asthma

Abstract: ClinicalTrials.gov Identifier: NCT01854047.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 20 publications
0
32
0
3
Order By: Relevance
“…23 The overall proportion of responders in the placebo group was high but comparable with observations from studies of other biologic treatments for asthma, in which the proportions of placebo group patients achieving clinically meaningful improvements in ACQ-6 and AQLQ(S)+12 scores were 61-78% and 70-77%, respectively. [31][32][33][34] It can be hypothesized that the high proportion of placebo group responders in these studies may be a result of increased J o u r n a l P r e -p r o o f adherence to standard-of-care treatments while participating in the studies. Additionally, several studies have demonstrated that the perceived benefits of clinical trial enrollment from the patient's perspective can induce a positive response to a placebo treatment.…”
Section: Discussionmentioning
confidence: 99%
“…23 The overall proportion of responders in the placebo group was high but comparable with observations from studies of other biologic treatments for asthma, in which the proportions of placebo group patients achieving clinically meaningful improvements in ACQ-6 and AQLQ(S)+12 scores were 61-78% and 70-77%, respectively. [31][32][33][34] It can be hypothesized that the high proportion of placebo group responders in these studies may be a result of increased J o u r n a l P r e -p r o o f adherence to standard-of-care treatments while participating in the studies. Additionally, several studies have demonstrated that the perceived benefits of clinical trial enrollment from the patient's perspective can induce a positive response to a placebo treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent post-hoc analysis of a phase 2 study (NCT01854047), dupilumab produced a significant and clinically meaningful improvement in asthma symptom control as assessed via ACQ-5, AM/PM Asthma Symptoms Score, QoL, and productivity in an intention-to-treat population who received the drug administered at a dose of 200/300 mg every 2 weeks [62]. Another post-hoc analysis of the same study (NCT01854047) indicated that dupilumab 200 mg and 300 mg administered every 2 weeks significantly (P \ 0.05) reduced the rate of severe exacerbations and significantly (P \ 0.05) improved lung function, asthma control, and QoL compared to placebo, regardless of the exacerbation history of the patient [63].…”
Section: Dupilumabmentioning
confidence: 99%
“…In patients with a FeNO of 50 ppb or more, the difference as compared with matched placebo was 0.39 liters. In a post hoc analysis, the greatest treatment benefit as compared with placebo was observed in patients with elevated type 2 biomarkers (both baseline blood eosinophil count of ≥150 per cubic millimeter and baseline FeNO ≥25 ppb) 44 .…”
Section: Dupilumabmentioning
confidence: 95%